Export Linking Public Institutions of Higher Education (Business Schools), State Trade Agencies and Private Enterprise: A Model and Method for Scaling Global Trade - Wood, Van (Archives of Business Research, 2021)
Abstract: In 2015, the Governor of the Commonwealth of Virginia, Mr. Terry McAuliffe, accepted the advice of companies that were located in Virginia who said they could use state support to export their goods and services. From this discussion, a the Virginia International Trade Alliance (VITAL) was created to help those companies expand and succeed in the international marketplace (see - https://augustafreepress.com/governor-mcauliffe-announces-creation-of-virginia-international-trade-alliance/ ) This initiative is now managed by Virginia’s Department of Commerce (through its economic development agency, known as the Virginia Economic Development Partnership - VCDP). Over the last 5 years, in partnership with Virginia private businesses, the state’s Chamber of Commerce, and Virginia’s public institutions of higher education, the program has created public-private partnerships that benefit – 1) large, medium and small companies (with strategic access to global markets), 2) public universities (particularly participating business schools that are educating the next generation of savvy international business managers), and 3) Virginia itself (with more tax revenues realized from enhance international trade, more jobs related to such trade, and more awareness of the Virginia “brand” around the world, as traded goods and services from Virginia become better known and appreciated). In short, meaningful and well thought out public-private partnerships have led to “win-win” realities for all involved . Virginia Commonwealth University School of Business (VCU-SB) has participated in this program (along with 9 other public Virginia universities) since the inception of VITAL, and to-date the VCU-SB has undertaken over 25 graduate business student VITAL projects (see - https://business.vcu.edu/centers-institutes-and-labs/center-for-international-business-advancement/ ). Each project has focused on analyzing and selecting international markets for private Virginia companies, and advising them with respect to marketing strategies in promising global markets. This has all taken place, while also educating VCU-SB’s participating graduate students on the nuances of global market analysis, and strategies and management practices related to global business success. This conceptual paper represents an overview of how VITAL projects are selected, researched and completed. The paper provides series of figures to highlight the theory, practice and necessary steps related to VITAL’s success. The paper concludes with a call for other states and other countries to create their own form of VITAL (in general, labeled Vibrant International Trade Alliances) and to extend the underlying partnerships that this model represents to like-minded entities around the world. The overall objective is to develop a global network of public/private linkages to scale global trade even further.